Valorização do magistério da educação básica no RN: participação do SINTE e do governo estadual na implementação do piso salarial profissional nacional na rede pública estadual no ano de 2009 - Ferreira, Maria Aparecida dos Santos (2010)
This paper analyzes the policy of upgrading the teaching profession in relation to financing basic education, with a view to participation of the Union of Education Workers of Rio Grande do Norte - SINTE / RN and the state government in the implementation of Professional Base Salary the National Professional Teaching Public Basic Education - Law 11738/2008, the public state of Rio Grande do Norte. The participation of civil society, through the union movement presents itself as an important process of implementation of Professional Base Salary. The participation of SINTE / RN occurred since the fight to pass the plan, careers and Compensation (2006) until the implementation of the Base Salary (2009) highlighting the power relations established between the Union and State Government. To this end, there were actions such as public hearings and strikes by education professionals. In order to raise issues relevant to the issue of enhancement of teaching and participation of unions as a collective representation has been taken as a theoretical and methodological literature on the financing of basic education, enhancing teaching and participation as well as policy guidelines governing the career of teaching. Was used as a methodological procedure to document analysis and information gathering through semi-structured interviews. The results indicate the participation and the power relationship between the trade union movement and the state government in the implementation of the Base Salary. However, the current issues concerning the limitations of recovery of the teaching profession in order to implement the policy floor, not only merit of the state of Rio Grande do Norte, but the decisions that have been taken by the Supreme Court (STF) relating to the unconstitutionality of Action (ADI) filed by five governors. This fact greatly reduced the possibility of recovery of the teaching of the state, considering that the government was limited to decisions of the Supreme Court. Therefore, the enhancement of teaching remains a challenge for the union movement